Pelatihan Uji Sentuh Jari Kaki Sebagai Upaya Peningkatan Ketrampilan Kader Kesehatan Dalam Mendeteksi Gangguan Sensasi Kaki - Suyanto Suyanto; Sri Lestari Dwi Astuti (Poltekkes Kemenkes Surakarta, 2021)
Background: Increased life expectancy will be followed by increasing problems if health care is not carried out properly. Problems will arise, one of which is endocrine system disorders such as diabetes mellitus which has complications. One of the complications of diabetes mellitus is diabetic ulcers on the feet by 7.5% of patients who experience impaired sensation which ultimately have to undergo amputation. This condition can be prevented early, such as by checking the sensation of the feet. This activity aims to increase the role of health cadres in detecting the incidence of neuropathy. Methods: In order to provide knowledge and skills of the toe touch test to 30 health cadres, the method chosen was training supported by guidebooks, videos and demonstrations. Results: There was an increase in the knowledge of cadres in good categories from 13% to 89% between before and after training. Meanwhile, the skills of the cadres showed that all of the training participants were skilled in doing the toe touch test. Conclusion: Improving the knowledge and skills of cadres can be pursued through training by combining the use of manuals, videos and demonstrations.